PREVALENCE AND DEGREE OF SEVERITY OF ACNE VULGARIS IN STUDENTS OF MECHANICAL ENGINEERING MAJOR IN FACULTY OF ENGINEERING DIPONEGORO UNIVERSITY - Saragih, Yola Valentin; Widyawati, Widyawati; Utami, Aras; Antari, Arlita Leniseptaria (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2019)
Introduction : Acne vulgaris (AV) is a chronic inflammatory disorder of pilosebaceous follicle with polymorphic dermatological manifestation such as comedones, papules, pustules, nodules, and scar. Acne vulgaris can be categorized into three degrees of severity based on lesions count: mild, moderate, and severe. There are four factors in the pathogenesis of AV: pilosebaceous follicle hyperproliferation, excessive sebum production, inflammation, and presence of Propionibacterium acnes. The degree of severity is mainly related to the number of an individual's sebaceous gland. Individuals with AV usually have large sebaceous glands that are very active, large pores, and oily skin. Objectives : To describe prevalence and severity of acne vulgaris in students of mechanical engineering major in faculty of engineering Diponegoro University batch 2018. Methods : This is an observational study with cross sectional approach in which author describes prevalence of AV and its degree of severity in students of mechanical engineering major in faculty of engineering diponegoro university batch 2018. Subjetcs were obtained from simple random sampling. There were 71 eligible subjects meeting inclusion criterias. Dermatovenereology residents performed physical examination on subjects to determine whether or not the subject had. Subjects with AV were classified into "positive" group, otherwise "negative". Subjects were obtained with simple random sampling technique. All subjects (100%) had acne vulgaris. Severity of AV varies with 38% subjects had mild AV, 59.2% had moderate AV and 2.8% had severe AV.Conclusions : All subjects (100%) had AV, mostly of moderate severity. Keywords : Acne Vulgaris; prevalence; severity